Interactive safety railway through gamification learning education activities / Norsyazwana Jenuwa, Abdul Muhaimin Ab. Wahid, Mohd Amir Rashdan Mat Kashim ... [et al.] - Jenuwa, Norsyazwana; Ab. Wahid, Abdul Muhaimin; Mat Kashim, Mohd Amir Rashdan; Yusop, Norhafizah; Ali, Suhaila (2024)
Game-based learning is an important approach that improves student engagement, creativity, critical thinking, and problem-solving skills. The integration of gamified learning activities in railway safety education can revolutionize training methods by enhancing engagement and knowledge retention. Gamification in safety training offers several benefits, including increased awareness, the creation of a safety-conscious culture, the opportunity for learners to practice safety procedures in realistic scenarios, and the reinforcement of progress through instant feedback loops. Additionally, serious games and gamification elements can provide an immersive and safe environment for learners to practice their skills, fostering behavioral changes crucial for safety training effectiveness. In the context of railway safety education, gamification can involve an awareness about the hazard at railway stations. Overall, the gamification of safety training in the railway industry can actively engage learners in various interactive ways, promote compliance with safety protocols, and enhance the overall safety culture within railway safety education.